2020
DOI: 10.1088/1755-1315/454/1/012147
|View full text |Cite
|
Sign up to set email alerts
|

GIS based: mapping of Multy Purpose Tree Species (Durio zibethinus) in Perkebunan Tambunan Village, Langkat District, North Sumatera Province, Indonesia

Abstract: Durio zibethinus (durian) in Indonesia is known as one of the types of Multy Purpose Tree Species (MPTS). Durian is a Malvaceae family. It grows naturally as well as is planted on community agroforestry land in Langkat Regency, North Sumatra. This study aimed to map the distribution of land suitability of Durio zibethinus using Geographic Information System (GIS) in Perkebunan Tambuan Village, Salapian Sub district, Langkat District. This study was conducted from February 2019 to July 2019 at the USU Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Figure 1 showed the analyzed land cover changes in Kultalimbaru Sub-district by overlaying the 2009 and 2019 land cover maps using GIS. The GIS applications have been carried out in several studies in several areas [12][13][14][15][16]. 2 showed that the difference in land cover changes occurring in mixed gardens decreased by 2,962.19 ha, then oil palm plantation increased by 1,587.12 ha, and open land increased by 935.87 ha.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 showed the analyzed land cover changes in Kultalimbaru Sub-district by overlaying the 2009 and 2019 land cover maps using GIS. The GIS applications have been carried out in several studies in several areas [12][13][14][15][16]. 2 showed that the difference in land cover changes occurring in mixed gardens decreased by 2,962.19 ha, then oil palm plantation increased by 1,587.12 ha, and open land increased by 935.87 ha.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 analyzed land cover changes in the Kultalimbaru Sub-District by overlaying GIS's 2009 and 2019 land cover maps. GIS applications have been carried out in several studies in several areas [12][13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the number of accessions added, the constant value of genetic diversity indicates that the plant germplasm is genotypically uniform. Indonesia has various sources of germplasm of fruit plants with high genetic diversity (Retnoningsih et al 2011;Retnoningsih et al 2014;Rahmawaty et al 2019;Fitmawati et al 2020;Sembiring et al 2020;Suwardi et al 2020;Tolangara et al 2020). The results showed that durian genetic diversity was high even though the study was limited to the Gunungpati area; 16 durian varieties showed different genotypes in D. zibethinus.…”
Section: Polymorphism Of Issr Superior Durian Gunungpati Allelementioning
confidence: 99%